Dynamics of the Ministry of Religious Affairs in Managing Prayer Schedules in Indonesia - Ismail, Ismail; Kamilan, Ikhsan (Syarah: Jurnal Hukum Islam dan Ekonomi, 2023)
Indonesia is one of the religious countries that regulates the issue of public worship. This paper tries to establish the dynamics of the Ministry of Religion in regulating prayer schedules in Indonesia. With a normative approach, it is expected to find the role, authority and function of the Ministry of Religious Affairs in regulating prayer schedules in Indonesia.  From the explanation of the Law and Regulation of the Minister of Religious Affairs, it can be concluded that there are three main tasks of the Ministry of Religious Affairs in the issue of hisab rukyat, namely preparation, implementation, and evaluation.  From these three main tasks, it can be concluded that the role of the Ministry of Religious Affairs is also normative, namely controllers, facilitators, and legislators. In the view of the sociology of knowledge, the role of the Ministry of Religious Affairs as an institution that gives birth to legitimacy on the issue of prayer time in Indonesia must be seen in the process of legitimacy operatively in the social context. Ideally, the institution of the Ministry of Religious Affairs in giving birth to legitimacy for prayer times becomes new knowledge information or creates new knowledge in the social space of science, but at this time it still seems to strengthen the knowledge of one of the existing knowledge, even tends to only support knowledge that is already strong.